PENERAPAN METODE JIGSAW UNTUK MENINGKATKAN KUALITAS HASIL BELAJAR IPS - ANIK BIDAYATUL HIDAYAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Observations in class VIII-G MTsN 5 Jombang show that students' attention to the teacher is passive. When learning 25% of students in the class are relatively noisy, read books when the teacher is explaining, and talk alone with their peers. In discussion activities students lack concentration, do not immediately form groups and attention is focused on equipment. Student involvement in discussion is less visible, when questioning. Based on the description of the background of the research problem, the purpose of this research is to improve the quality of social studies learning outcomes in class VIII-G MTsN 5 Jombang in understanding the arrival of western nations to Indonesia through the implementation of the Jigsaw method of learning. The findings of this study indicate that in cycle I an average score of 75.2 was obtained and as many as 17 students (56.67%) had achieved mastery learning while 13 students (43.33%) had not achieved learning completeness. The average score of student activity reaches 2.55 which indicates an adequate category while the average score of teacher activity reaches 2.6 which is sufficient. Whereas in cycle II the student learning outcomes were obtained with an average score of 83.5 with learning completeness reaching 86.67% or as many as 26 students while 4 students (13.33%) did not achieve learning mastery scores. The average score of student activity reached 3.55 which was in the good category while the average score of teacher activity reached 3.5 which was in the good category. This study explains that there is an increase in the quality of student learning outcomes by using the Jigsaw method. The results showed that learning jigsaw could improve the quality of student learning outcomes in class VIII-G MTsN 5 Jombang, as evidenced by the results of the learning outcomes assessment score increasing from cycle I to cycle II. Besides that, this learning was able to increase the activeness of student learning, measured by the involvement of students in group discussions, which increased from cycle I to cycle II. It is suggested to teachers to use the jigsaw learning model to improve the quality of student learning outcomes in social studies learning, especially for teachers who have student characteristics and similar material. ABSTRAKHasil pengamatan di kelas VIII-G MTsN 5 Jombang menunjukkan bahwa perhatian siswa terhadap guru pasif. Ketika pembelajaran 25% siswa di kelas relatif gaduh, membaca buku ketika guru menerangkan, dan berbicara sendiri dengan teman sebangkunya. Dalam kegiatan diskusi siswa kurang konsentrasi, tidak segera membentuk kelompok dan perhatian terpusat pada perlengkapannya. Keterlibatan siswa dalam diskusi kurang terlihat, ketika tanya jawab. Berdasarkan uraian latar masalah penelitian, tujuan penelitian ini adalah untuk meningkatkan kualitas hasil belajar IPS pada siswa kelas VIII-G MTsN 5 Jombang dalam memahami Kedatangan bangsa barat ke Indonesia melalui pelaksanaan pembelajaran metode Jigsaw. Dari hasil temuan penelitian ini menunjukkan bahwa pada siklus I diperoleh nilai rata-rata sebesar 75,2 dan sebanyak 17 siswa (56,67 %) sudah mencapai ketuntasan belajar sedangkan 13 siswa (43,33 %) belum mencapai ketuntasan belajar. Skor rata-rata aktivitas siswa mencapai 2,55 yang menunjukkan kategori cukup sedangkan skor rata-rata aktivitas guru mencapai 2,6 yang berkategori cukup. Sedangkan pada siklus II diperoleh hasil belajar siswa dengan nilai rata-rata sebesar 83,5 dengan ketuntasan belajar mencapai 86,67 % atau sebanyak 26 siswa sedangkan 4 siswa ( 13,33 %) tidak mencapai nilai ketuntasan belajar. Skor rata-rata aktivitas siswa mencapai 3,55 yang menunjukkan berkategori baik sedangkan skor rata-rata aktivitas guru mencapai 3,5 yang berkategori baik. Penelitian ini menjelaskan bahwa adanya peningkatan kualitas hasil belajar siswa dengan menggunakan metode Jigsaw. Hasil penelitian menunjukkan bahwa pembelajaran jigsaw dapat meningkatkan kualitas hasil belajar siswa kelas VIII-G MTsN 5 Jombang, terbukti dengan hasil skor penilaian hasil belajar meningkat dari siklus I ke siklus II. Disamping itu pembelajaran ini ternyata dapat meningkatkan keaktifan belajar siswa diukur dari keterlibatan siswa dalam diskusi kelompok meningkat dari siklus I ke siklus II. Disarankan kepada guru agar menggunakan model pembelajaran jigsaw untuk meningkatkan kualitas hasil belajar siswa dalam pembelajaran IPS, khususnya kepada guru yang memiliki karakteristik siswa dan materi sejenis.